The Personal Papers of American Sailors, 1890s–1940s - Tummino, Annie (Archivaria)

(untitled) (Association of Canadian Archivists, 2022)
Personal papers in the archives at Maritime College, State University of New York, document the lives of alumni from the school’s founding in 1874 through the early decades of the 20th century. Journals, diaries, memoirs, and reminiscences located in these collections provide evidence of what it was like to work on a ship, far from home, travelling to foreign lands. In this article, I explore first-hand accounts of maritime life by Van Horne Morris, my maternal grandfather and a 1938 graduate of the Massachusetts Nautical School (now known as Massachusetts Maritime Academy), and several alumni of the New York Nautical School (now known as SUNY Maritime College), who graduated between 1896 and 1929. Close reading of their letters and manuscripts reveals echoes of a maritime literary tradition rooted in the antebellum-era United States. Comparing and contrasting the style and content of their writing to antecedents in the 19th century also illuminates continuity and changes in maritime labour and culture over time.